The Role of Social Media in Increasing Consumer Trust: Observational Analysis in PT United Waru Biscuit Manufactory Products - Saputra, Mochamad (LPPM Institut Bisnis dan Informatika Kesatuan, 2023)
This research investigates the role of social media in enhancing consumer trust in PT United Waru Biscuit Manufactory products. Employing a descriptive qualitative research method, data were collected through interviews and observations, focusing on social media dimensions. The qualitative approach aims to provide in-depth insights into the phenomenon under study. Three informants who had purchased products from PT United Waru Biscuit Manufactory participated in the study. The findings reveal that social media significantly contributes to building consumer trust in PT United Waru Biscuit Manufactory products. Consumer belief in a product is identified as a crucial factor influencing purchasing decisions. The study concludes that a successful social media presence positively correlates with increased consumer trust. Notably, the research suggests that PT United Waru Biscuit Manufactory could enhance its social media strategies by advertising on popular platforms such as TikTok, YouTube, Instagram, and television. Furthermore, endorsing influencers or artists is recommended, considering their substantial influence on society, particularly among followers. In conclusion, the research emphasizes the pivotal role of social media in shaping consumer trust. The implications for PT United Waru Biscuit Manufactory include diversifying advertising strategies to reach a broader audience and leveraging influencers to foster increased consumer trust. This study provides valuable insights for companies aiming to strengthen their brand perception through effective social media engagement.